Emigrantes brasileiros qualificados no Canadá - Morini, Ana Maria (2021)
This dissertation intends to collaborate with the debate on the migratory phenomenon, especially of qualified Brazilian emigrants in Canada. The main objective of the research is to understand the Canadian immigration policy and analyze how the migratory context proved to be determinant in the insertion in the labor market of these individuals. The literature points out that many immigrants, despite having technical and professional training, are unable to work within their qualification area. Thus, the hypothesis that guided this research is that qualified Brazilian emigrants in Canada find it difficult to get jobs compatible with their qualifications. However, these immigrants find in the country better conditions than they had in Brazil, both in terms of quality of life and financial return. Interviews were carried out with 15 qualified Brazilians who live and work in Canada, which sought to raise basic profile data, such as gender, age, place of birth, academic background, their professional experiences in Brazil and Canada, the motivations and procedures made for emigration. It is, therefore, an empirical research, of an exploratory nature, where bibliographic, documental and field survey methods were used, which led to the production of qualitative data. Therefore, this dissertation confirmed the hypothesis raised, that is, that qualified Brazilian emigrants in Canada find it difficult to get a job compatible with their qualification